The Experiences of Students with Foster Care Histories Attending Christian Universities - Lopez, Kizzy M. (Christian higher education, 2025)
The existing literature on college students with foster care histories almost exclusively addresses secular higher education. Of the roughly 4,000 colleges and universities in the United States, nearly 1,000 are religious based institutions, and over 150 campuses are part of the Council of Christian Colleges and Universities (CCCU) in the United States and Canada. However, little to no attention has been given to the experiences of students with foster care histories attending Christian universities. This study examines the lived experiences of such students. In-depth interviews were conducted with seven participants attending three residential Christian universities in two states in the western United States. Five themes emerged from the study: (1) identifying the factors that influenced students’ decision to attend a Christian university, (2) the impact of trauma and how it influenced students’ relationship with God and the Christian faith, (3) students’ foster care experience and how it shaped their identity development while in college, (4) students’ transition into college, and (5) the emotional navigation students undergo with familial relationships. We conclude with practical recommendations that Christian colleges and universities can implement to better support students with foster care backgrounds considering their unique needs.